TrackerSense : an entrepreneurial marketing start-up - O'Brien, Justin ([London] : SAGE, 2016)
This entrepreneurial marketing case study focuses on serial entrepreneur Wayne Soutter and his current technology start-up TrackerSense, which produces a low-cost mobile tracking device for high-value packages.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; New business enterprises -- Case studies; Marketing -- Case studies; Entrepreneurship -- Case studies; Automatic tracking -- Case studies; Packing for shipment -- Technological innovations -- Case studies; Shipment of goods -- Technological innovations -- Case studies